(untitled) (Swiss Medical Weekly, 2001)
An increasing amount of medical scientific information is published in specialised journals on various subjects, including complementary and alternative medicine (CAM). There are indications that positive findings may be published at the expense of methodological rigour. The aim of this investigation was to provide a profile of CAM journals currently available on Medline, and monitor trends in publication practice between the years 1995 and 2000. Systematic literature searches were performed to identify all CAM journals indexed in Medline. Journals published in 1995 and 2000 were identified by their title and content. Primary CAM research journals only were included in this analysis. All articles were read, data were extracted and categorised according to pre-defined criteria, e.g. type of methodology used, subject area, and direction of outcome. The number of original articles increased from a total of 61 in 1995 to 97 in 2000 across all four journals, the number of papers reporting clinical trials decreased by 4% between 1995 and 2000, and the number of surveys increased more than six times. Less positive and more negative articles were published in 2000 compared with 1995. The subject areas of papers varied greatly. The majority of articles published in 1995 suggested positive treatment effects, a phenomenon that was still present in 2000 albeit less strong. CAM journals, and most likely CAM itself, are associated with a lack of clinical trials and a bias in favour of positive conclusions.